Strong support for a universal basic income, in particular among those who would benefit - Marius R. Busemeyer; Adrian Rinscheid; Jürgen Schupp (DIW Weekly Report, 2023)
A representative survey from August 2022 confirms public support for a universal basic income (UBI): Between 45 and 55 percent of respondents are in favor of a universal basic income and the unconditional financial security it promises. Two representative surveys from August 2022 investigate who exactly UBI supporters are and which UBI model they prefer. The surveys show that younger people in particular as well as low-income earners and people with serious concerns about their own economic situation support a UBI. One of the surveys analyzed in this Weekly Report shows that most respondents support an unconditional UBI of 1,200 euros that is financed via higher income and wealth taxes on the rich.
Keywords: D63; I38; H23; 330; SOEP; Basic income-Preferences; Survey